الرؤية النقدية للفكر الصوفي عند بديع الزمان سعيد النورسي - رحمون, أسامة (University of Eloued جامعة الجزائر, 2020)
ولد سعيد النورسي في عصر انحطاط الدولة الإسلامية وتفككها، وانهيارها في جميع المجالات، مما كان له الأثر الإيجابي في تكوين شخصيته القوية، ونظرته الثاقبة في معرفة الداء وكيفية علاجه، فأصبح من كبار المصلحين والمجددين في العالم الإسلامي، حيث رصد ملامح الإصلاح في الفكر الصوفي الحديث، الذي عُرف بتعدد المناهج والطرق لمروره بمراحل متعددة، فهو نتاج جهود فكرية بشرية متعددة مرّت بعصور وأزمان مختلفة، لكن هذا الفكر خالطه الكثير من البدع والشبهات جعلته لا يتماشى مع العصر الحديث، فانبرى له جملة من الدعاة المصلحين المجددين كسعيد النورسي الذي كرّس حياته وجهوده في خدمة الإسلام والمسلمين، وفي إعادة إحياء التصوف وتقويم مساره بأسلوب جديد قائم على الكتاب والسنة، متماشيا مع العصر الحديث الذي طغت عليه الأفكار المادية المنحرفة الهدامة كالإلحاد والعلمانية وغيرها، فالنورسي دعا إلى التمسك بالوحيين والإقتداء برجال العصر الأول للإسلام، فهم النموذج الأمثل للتصوف عنده، لإخراج هذه الأمة من الظلمات إلى النور، ومن الإنحطاط إلى الرقي.Said Nursi was born in the era of the decline and disintegration of the Islamic state, and its collapse in all areas, which had a positive impact on the formation of his strong personality, and his insight into knowing the disease and how to treat it. He became one of the leading reformers and innovators in the Islamic world, as he monitored the features of reform in modern Sufi thought, which was known for its multiple approaches and methods as it passed through multiple stages, as it is the product of multiple human intellectual efforts that have gone through different eras and times. However, this thought was mixed with many innovations and suspicions that made it not in line with the modern era, so a group of reformist and innovative preachers emerged, such as Saeed Al-Nursi, who devoted his life and efforts to serving Islam and Muslims, and in reviving Sufism and correcting its path in a new method based on the Qur’an and Sunnah, in line with the modern era. Who was overshadowed by destructive, deviant materialistic ideas such as atheism, secularism and others, Al-Nouri called for adhering to the revelations and imitating the men of the first era of Islam, for they are the ideal model for Sufism for him, to bring this nation out of darkness into light, and from decline to sophistication
مذكرة ماستر تخصص عقيدة
Keywords: الصوفية /التصوف/ النقد /الطريقة; " Sufism Mysticism criticism Way"